Pengaruh Faktor Free Cash FLow dan Leverage terhadap manajemen Laba: Literature review - Daniel Nemba Dambe; Budi Prijanto; Longginus Gelatan; Klemens Mere; Jemi Pabisangan Tahirs (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The purpose of this article is to analyze the influence of the Free Cash Flow and Leverage factors on earnings management through an analysis of literature reviews in the field of financial management. The method used in this study is a literature study by reviewing some of the results of previous studies. The writing approach in this scientific article is to use qualitative methods and library research with the help of the latest references obtained from Google Schoolers and Mendeley citation searches. The results of previous studies were analyzed and used as reference material to determine answering the existing hypotheses. The results of the literature review show that the Free Cash Flow factor has two results, namely it can influence and does not significantly influence earnings management within the company, as well as Leverage which can sometimes give positive results on earnings management, but can also have a negative effect on earnings management. Keywords: Free Cash Flow, Leverage, Literature Review, Earnings Management